AERATION EFFICIENCY OF A THREE-PHASE FLUIDIZED BED BIOREACTOR DURING FOOD INDUSTRY WASTEWATER TREATMENT - Manyele, S. V.; Halfani, M. R.; Benjamin, Y. (Tanzania Journal of Engineering and Technology, 2018)
Abstract